GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 2558 species occurrences available in GBIF matching the query: TaxonKey: 2462721 Geometry: POLYGON((165.59 -80.36,165.59 79.87,-113.55 79.87,-113.55 -80.36,165.59 -80.36)) HasGeospatialIssue: false. The dataset includes 2558 records from 67 constituent datasets: 96 records from KUBI Herpetology Collection. 10 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 2 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 2 records from Herpetofauna del corredor biológico Chichinautzin y la Sierra de Huautla en el estado de Morelos. 1 records from PSM Vertebrates Collection. 2 records from Bernice P. Bishop Museum. 2 records from Herp Collection. 17 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 336 records from Formación de una base de datos y elaboración de un atlas de la herpetofauna de México. 54 records from UCM Amphibian and Reptile Collection (Arctos). 53 records from Australian Museum provider for OZCAM. 3 records from Queensland Museum provider for OZCAM. 8 records from Herpetology Collection - Instituto Nacional de Pesquisas da Amazônia. 108 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 6 records from Colección de anfibios y reptiles del Laboratorio de Herpetología de la Universidad del Valle (UV-C). 21 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 2 records from SysTax - Zoological Collections. 9 records from Western Australian Museum provider for OZCAM. 1 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 130 records from MVZ Herp Collection (Arctos). 1 records from CUMV Reptile Collection (Arctos). 14 records from Colección Herpetológica del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 1 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 3 records from Arizona State University Amphibian and Reptile Collection. 2 records from NRM-Herpetology. 3 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 1 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 1 records from herpetology. 4 records from Occurrences in SinBIOTA. 267 records from CAS Herpetology (HERP). 4 records from Colección de Reptiles del Instituto Alexander von Humboldt. 478 records from NMNH occurrence DwC-A. 2 records from Northern Territory Museum and Art Gallery provider for OZCAM. 6 records from Anfibios y Reptiles reportados en humedales del departamento de Córdoba. 6 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 6 records from Herpetofauna laguna El Tinije. 3 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 2 records from iNaturalist research-grade observations. 2 records from UAM Herpetology Collection (Arctos). 15 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 6 records from SMNS Herpetologie. 9 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 26 records from Herpetology Collection - Royal Ontario Museum. 7 records from Collection Herpetology SMF. 1 records from Natural History Museum (London) Collection Specimens. 5 records from RBINS collections. 1 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Herpetofauna. 3 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 1 records from IndOBIS, Indian Ocean Node of OBIS. 43 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 141 records from Reptile Specimens. 18 records from CM Herps Collection. 1 records from Formación de la colección de referencia de anfibios y reptiles de la Reserva de la Biosfera de Sian Ka'an. 1 records from NCSM Herpetology Collection. 3 records from UTEP Vertebrates. 3 records from Reptiles del Estado de Veracruz.. 2 records from naturgucker. 164 records from LACM Vertebrate Collection. 112 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 40 records from Ditsong Museum. 5 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 10 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 8 records from SDNHM Herpetology Collection. 3 records from South Australian Museum Australia provider for OZCAM. 258 records from Museum of Comparative Zoology, Harvard University. 2 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2. 1 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México.
Keywords: GBIF; biodiversity; species occurrences